Perspective method for removing heavy metals from underground waters of Western Ukraine - Yuliia Trach (Acta Scientiarum Polonorum. Architectura)
The largest group of recipients of the drinking water from groundwater in Ukraine are resides in the western part of the country. Due to the presence of zones in which the water-resistant rocks are subject to cracking in the hydrogeological regions of the Western Ukraine, the physicochemical composition of water is not constant and may vary, especially in terms of heavy metals content. The reasons for the presence of heavy metals in the groundwater are the anthropogenic influence and biological leaching of mineral ores. Heavy metals can migrate up and down and penetrate the aquifers of drinking water through the cracked zones of the waterresistant rocks. The mineral ores found in the Western Ukraine contain heavy metals, mainly as sulfides. They are oxidized by thionic bacteria (рН 5–7). As a result, the concentration of sulfate in water increases. At the same time, in the Western Ukraine, natural materials containing aluminosilicates such as zeolites, tuffs, basalts and others are widely distributed. They can be used as sorbents in the process of groundwater treatment. When using aluminosilicates, the removal efficiency is higher than in the case of traditionally used slacked lime (Ca(OH)2) due to the fact that heavy metals are extracted by means of two mechanisms – ion exchange and formation of insoluble bases.